High-strength pavement repairing mortar
By using high-strength pavement repair mortar and using specific ratios of cement, aggregate and nanomaterials, the problem of insufficient strength at the joints of existing repair mortars is solved, and the road surface strength and longer service life are achieved, and the self-repair ability is achieved.
Patent Information
- Application Number
- CN202510021482.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-11
AI Technical Summary
The existing pavement repair mortar has poor strength at the joints between the old and new pavements after solidification, resulting in a lower pavement life at the repaired pavement.
High-strength pavement repair mortar is used, which includes components A and components B. Component A is composed of cement, aggregate, water reducing agent, dispersible latex powder, cellulose, defoaming agent, tartaric acid and water. Component B includes waste soot and preferred three-dimensional nanocomposite materials.
The strength and compactness of the road surface after repair is improved, the road surface life of the repaired place is extended, and the self-repairing ability of the mortar is enhanced.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of building materials, and in particular to high-strength road repair mortar. Background Art
[0002] Most of my country's rural roads are paved with cement concrete. With the increasing number of vehicles in my country, some cement roads have become exhausted. The damage of cement roads is usually manifested in potholes, spalling (the surface material of Lumina falls off), cracks, etc.
[0003] The crushing of cement roads will have a certain impact on driving comfort and anti-skid performance of the road surface. Therefore, when the road surface is crushed, it needs to be repaired in time to reduce further damage to the road surface and reduce the risk of formation.
[0004] Usually, the road surface is repaired by using mortar, which is generally formed by mixing cement and sand in a certain proportion. The mortar is filled in the damaged part of the road surface and then smoothed to achieve the repair of the road surface.
[0005] Although conventional mortar can be used to repair the road surface, the strength of the junction between the new and old road surfaces is poor after the mortar solidifies, resulting in a shorter road surface life at the repaired location. Summary of the invention
[0006] In order to increase the service life of the road surface after repair, the present application provides high-strength road surface repair mortar.
[0007] The high-strength pavement repair mortar provided in this application adopts the following technical solution:
[0008] High-strength pavement repair mortar, including component A and component B;
[0009] Component A is the main agent, and component B is the auxiliary agent;
[0010] Component A includes the following components by mass: 350-550 parts of cement, 400-500 parts of aggregate, 0.5-2.0 parts of water reducer, 2-5 parts of dispersible latex powder, 0.1-0.5 parts of cellulose, 0.5-2.0 parts of defoamer, 0.5-1.0 parts of tartaric acid, and 200 parts of water. The cement is composed of sulphoaluminate cement and silicate cement in the ratio of (4-6): (3-5). Component B includes the following components by mass: 3.5-5.5 parts of waste smoke.
[0011] Preferably, component B also includes: 2.5-5.5 parts of a three-dimensional nanocomposite material, and the mass ratio of silicon carbide to carbon fiber in the three-dimensional nanocomposite material satisfies (1.8-2.5):(0.8-1.3).
[0012] Preferably, the preparation method of the three-dimensional nanocomposite material includes: the first step, silicon carbide powder modification, adding nano-scale silicon carbide powder to 0.2g / mL NaOH solution, stirring at 85°C for 6h, washing with ethanol and deionized water until neutral, placing the cleaned nano silicon carbide powder in a vacuum oven at 85°C, and drying to obtain SiC-OH; taking the above-prepared SiC-0H and adding it to a mixture of anhydrous ethanol and distilled water, and ultrasonically dispersing it for 1h; adjusting the pH of the solution to 4-5 with formic acid, and then adding an appropriate amount of 3-aminopropyltriethoxysilane dropwise; stirring at 85°C for 24h to complete the reaction; washing with ethanol and distilled water three times, and then vacuum drying at 60°C to obtain SiC-OH@Kh550;
[0013] The second step is carbon fiber modification. An appropriate amount of carbon fiber is added to an appropriate amount of hydrogen peroxide solution with a mass fraction of 30 wt%, stirred at a constant temperature of 50 ° C for 6 hours, washed three times with ethanol and deionized water, and the cleaned carbon fiber is placed in a vacuum oven at a constant temperature of 60 ° C to dry to obtain CFs-COOH;
[0014] In the third step, (1.8-2.5) mass fraction of SiC-OH@Kh550 and (0.8-1.3) mass fraction of CFs-COOH were dissolved in distilled water and stirred at 85°C for 6 hours. After the reaction was completed, it was washed three times with ethanol and distilled water and dried in vacuum at 60°C to obtain a composite three-dimensional nanocomposite material.
[0015] Preferably, the dispersible latex powder is a copolymer of vinyl acetate.
[0016] Preferably, the aggregate comprises two river sands of different particle sizes, the particle sizes of the two river sands are 1-2 mm and 5-6 mm respectively, and the ratio thereof satisfies (1.5-2.5):(0.8-1.2).
[0017] Preferably, the fibers consist of steel fibers and flax fibers in a ratio of 2:4.
[0018] Preferably, the defoaming agent is polyether silicone oil.
[0019] Preferably, the three micro-nano materials are: SiC-OH@APTES-g-CFs-COOH; in order to improve the physical and mechanical properties of nanomaterial-reinforced resin-based composites, carbon fibers are treated with γ-aminopropyltriethoxysilane, and silicon carbide (SiC)@γ-aminopropyltriethoxysilane is self-assembled on the surface of carbon fibers to prepare a three-dimensional nanocomposite material. The three-dimensional nanocomposite material can form mechanical engagement with the aggregate, increase the contact area and contact layer thickness between the aggregate and the nanomaterial inside the sample, and effectively improve the chemical bonding and non-chemical bonding between the fiber and the matrix material, thereby effectively transferring stress when the sample is subjected to load and enhancing the interface performance between the substrate and the nano-doping.
[0020] Preferably, the waste smoke in the raw material needs to be processed. The specific processing process is: first, the flue gas generated by the electric furnace is separated from the dust with high specific gravity by a gravity cyclone dust collector; then the high-temperature flue gas is passed through a flue gas water cooling tower to reduce the temperature and further separate the dust. The temperature of the flue gas after passing through the flue gas circulating water cooling tower is 45°C to 245°C; then the flue gas is discharged into a pipeline into a flue gas purification chamber, and the dust in the flue gas is collected by a fluoromethoxy filter bag through a sub-bin purification chamber in the flue gas purification chamber, and finally processed by a vortex centrifuge to obtain gaseous active silica powder; the gaseous active silica powder is sent to a powder storage tank for storage, and is treated and recovered at a temperature exceeding 100°C to obtain active silica powder; then the silica powder is modified, and the specific process is: 1. A tetrahydrofuran solution of polydimethylsiloxane is prepared, wherein the mass concentration of polydimethylsiloxane is 2-8wt%. 1. Disperse spherical silicon micropowder in the solution, and the dispersion ratio of spherical silicon micropowder in the solution is (1-4) g / 100 mL; 2. Filter out the silicon micropowder after stirring and mixing, and vacuum dry it; 3. Heat the dried silicon micropowder to 400-600°C and keep it warm for 0.5-1h, then cool it to obtain active silicon micropowder.
[0021] Since there are a lot of Ca(OH)2 and free Ca in cement 2+ Mg 2+ Alkaline substances are soluble in water. Excessive amounts of these substances may affect the performance of mortar. Reducing their content through chemical reactions can not only improve the strength of mortar, but also enhance the compactness of mortar. The active ingredients of active silica powder react with Ca(OH)2 and free Ca2+, Mg2+ and other substances in cement at specific concentrations and osmotic pressures. With the action of water, these complexes diffuse into the mortar, and when encountering cement particles and cement gel, the active ingredients are replaced by more stable silicate ions to generate water-insoluble and more stable crystalline substances. Water-insoluble crystalline substances such as calcium silicate and magnesium silicate are produced to fill pores and cracks, thereby improving the compactness of concrete. In a dry state, this material is dormant, but when cracks occur in the repair mortar and water invades, the active ingredients will be activated, penetrate with water and react to generate healing products, automatically repairing microcracks and pores.
[0022] Preferably, the preparation process of the high-strength pavement repair mortar includes:
[0023] S1, preparation of mixture a, mixing silicate cement, sulphoaluminate cement, cellulose, dispersible latex powder, three micro-nano materials and active silicon powder at a temperature of 28.5° C. and a stirring speed of 20 r / min to obtain mixture a;
[0024] S2, preparation of mixture b, mixing water, tartaric acid and defoaming agent at a temperature of 28.5° C. and a stirring speed of 200 r / min, and stirring them uniformly to obtain mixture b.
[0025] S3, preparation of mixture c, adding sand into mixture a, mixing and stirring at a temperature of 28.5°C and a stirring speed of 20 r / min, to obtain mixture c.
[0026] S4, preparation of mortar, adding mixture b into mixture c, mixing and stirring at a temperature of 28.5°C and a stirring speed of 20r / min, the stirring time is 5min-10min, to obtain mortar.
[0027] Beneficial effects:
[0028] By adopting the above technical scheme, the surface of castor fiber is rough and has a strong chelating force with the cement matrix, thereby improving the strength of the mortar after solidification; the addition of steel fiber reduces the gaps between coarse aggregates, thereby improving the density of concrete, and the steel fiber and flax fiber cooperate with each other, the bonding force is enhanced, and the effect of hindering crack propagation is enhanced, while the curing shrinkage and microcracks caused by shrinkage are reduced, thereby improving the strength of the road surface.
[0029] By adopting the above technical solution, polyether silicone oil has excellent thermal stability and chemical corrosion resistance, can be used in extreme environments, and has good lubrication properties, which can improve the flowability of mortar and enable it to fill the gaps in old pavement.
[0030] The prepared three-dimensional nanocomposite material can form mechanical engagement with the aggregate, increase the contact area and contact layer thickness between the aggregate and the nanomaterial inside the sample, and effectively improve the chemical bonding and non-chemical bonding between the fiber and the matrix material, thereby effectively transmitting stress when the sample is under load, enhancing the interface performance between the substrate and the nano-doping, and improving the mechanical strength and rigidity of the repair mortar. DETAILED DESCRIPTION
[0031] The embodiments of the present application disclose high-strength pavement repair mortar.
[0032] High-strength road repair mortar includes 350kg of cement, 400kg of sand, 0.5kg of water reducer, 2kg of dispersible latex powder, 0.1kg of fiber, 0.5kg of defoaming agent, 0.5kg of tartaric acid and 200kg of water.
[0033] The cement is composed of sulphoaluminate and silicate in a mass ratio of 4:5; the sand is a mixture of river sand with a particle size of 1-2 mm and river sand with a particle size of 5-6 mm in a ratio of 2:1. The dispersible latex powder is a copolymer of vinyl acetate, and the fiber is composed of steel fiber and flax fiber in a ratio of 2:4. The water reducer is a polycarboxylic acid water reducer. The defoamer is polyether silicone oil.
[0034] The preparation process of the high-strength pavement repair mortar in this embodiment includes the following steps:
[0035] The preparation process of high-strength pavement repair mortar includes:
[0036] S1, preparation of mixture a, mixing silicate cement, sulphoaluminate cement, cellulose, dispersible latex powder, three micro-nano materials and active silicon powder at a temperature of 28.5° C. and a stirring speed of 20 r / min to obtain mixture a;
[0037] S2, preparation of mixture b, mixing water, tartaric acid and defoaming agent at a temperature of 28.5° C. and a stirring speed of 200 r / min, and stirring them uniformly to obtain mixture b.
[0038] S3, preparation of mixture c, adding sand into mixture a, mixing and stirring at a temperature of 28.5°C and a stirring speed of 20 r / min, to obtain mixture c.
[0039] S4, preparation of mortar, adding mixture b into mixture c, mixing and stirring at a temperature of 28.5°C and a stirring speed of 20r / min, the stirring time is 5min-10min, to obtain mortar.
[0040] Example 2-3
[0041] Examples 2-3 are high-strength pavement repair mortars with different raw material ratios. The raw material components of the high-strength pavement repair mortar corresponding to each example are described in the following table, and the raw material ratio unit is kg.
[0042] raw material Example 1 Example 2 Example 3 cement 350 450 550 sand 400 400 400 Water reducing agent 0.5 0.5 0.5 Dispersible latex powder 2 2 2 fiber 0.1 0.1 0.1 Defoaming agent 0.5 0.5 0.5 tartaric acid 0.5 0.5 0.5 water 200 200 200
[0043] The preparation process of the high-strength pavement repair mortar of Examples 2-3 is exactly the same as that of Example 1.
[0044] Example 4: This example is different from Example 2 in that the cement is composed of sulphoaluminate and silicate in a mass ratio of 5:4.
[0045] The preparation process of the high-strength pavement repair mortar in this embodiment is exactly the same as that in Example 1.
[0046] Example 5
[0047] The difference between this embodiment and embodiment 2 is that the cement is composed of sulphoaluminate and silicate in a mass ratio of 6:3.
[0048] The preparation process of the high-strength pavement repair mortar in this embodiment is exactly the same as that in Example 1.
[0049] Example 6, the difference between this example and Example 5 is that the water reducer is 1kg, and the water reducer is a silane-modified water reducer, and the rest is exactly the same as Example 5. The preparation process of the silane-modified water reducer comprises the following steps: 1. Mix allyl polyoxyethylene ether (HPEG), silane coupling agent (KH-570) and deionized water, stir, and heat to 40°C. 2. Dissolve acrylic acid, ascorbic acid and mercaptoethanol in deionized water to obtain a mixed solution 1. Dissolve ammonium persulfate in deionized water to obtain a mixed solution 2. 3. After all materials are dissolved, the monomer solution and the oxidant solution are added dropwise to the reaction bottle under a nitrogen atmosphere, and the dropping time is controlled to 3h. 4. After the dropwise addition is completed, keep warm for 2 hours, then cool the reaction to room temperature, adjust the pH value to 5 with a 32wt% NaOH aqueous solution, and dilute the polymer solid content to 40% with deionized water to obtain a finished product. In step 2, the amount of ascorbic acid used is 0.6-0.8.
[0050] The preparation process of the high-strength pavement repair mortar in this embodiment is exactly the same as that in embodiment 1.
[0051] Comparative Example: Table 2 shows the content of each component of the high-strength pavement repair mortar.
[0052]
[0053]
[0054] Comparative Example 1: In this comparative example, the cement is silicate cement. The other conditions are exactly the same as those in Example 1.
[0055] Comparative Example 2: In this comparative example, cement only includes sulphoaluminate cement, and the rest is exactly the same as in Example 1.
[0056] Comparative Example 3: This comparative example lacks a water reducing agent.
[0057] The mortars of Examples 1-6 and Comparative Examples 1-3 were used to conduct comparative tests on concrete compressive strength, flexural strength, elastic modulus and fluidity.
[0058] The compressive strength, flexural strength, elastic modulus and shrinkage performance of the high-strength pavement repair mortar are tested in accordance with GBT31387-2015 "Reactive Powder Concrete" and GBT 50081-2002 "Standard Test Method for Mechanical Properties of Ordinary Concrete".
[0059] The fluidity test method is to fill a specified steel mold with the mortar to be tested, then discharge the mortar from the bottom of the mold, and then use a 10 mm diameter and 50 mm high iron cone to push the mortar vertically downward in the center, and record the distance the iron cone sinks. The fluidity of the mortar can be determined based on the distance the iron cone sinks.
[0060] The experimental results are as follows:
[0061]
[0062] Combining Example 1 and Comparative Example 1, and combining Table 2, it can be seen that the cooperation between silicate cement and sulphoaluminate cement can shorten the setting time of cement, and facilitate rapid opening to traffic after power repair.
[0063] Combining Example 1 and Comparative Example 2, and combining Table 2, it can be concluded that Portland cement can delay the setting time of mortar, so that the mortar has a longer time to penetrate into the gaps of the damaged road surface, thereby improving the connection strength between the new and old road surfaces.
[0064] Combining Example 1 and Comparative Example 3, it can be seen that the water reducing agent can improve the fluidity of the mortar, allowing the mortar to further penetrate into the cracks of the old road surface.
[0065] Combining Examples 5 and 6, it can be seen that the addition of the modified water reducing agent further improves the fluidity of the mortar.
[0066] Example 7
[0067] Relative to Example 1, the preparation method of the three-dimensional nanocomposite material includes: the first step, silicon carbide powder modification, adding nano-scale silicon carbide powder to 0.2g / mL NaOH solution, stirring at a constant temperature of 85°C for 6h, washing with ethanol and deionized water until neutral, placing the cleaned nano-silicon carbide powder in a vacuum oven at a constant temperature of 85°C, and drying to obtain SiC-OH; taking the above-prepared SiC-0H and adding it to a mixture of anhydrous ethanol and distilled water, ultrasonically dispersing it for 1h; adjusting the pH of the solution to 4-5 with formic acid, and then adding an appropriate amount of 3-aminopropyltriethoxysilane dropwise; stirring at 85°C for 24h to complete the reaction; washing with ethanol and distilled water three times, and then vacuum drying at 60°C to obtain SiC-OH@Kh550;
[0068] The second step is carbon fiber modification. An appropriate amount of carbon fiber is added to an appropriate amount of hydrogen peroxide solution with a mass fraction of 30 wt%, stirred at a constant temperature of 50 ° C for 6 hours, washed three times with ethanol and deionized water, and the cleaned carbon fiber is placed in a vacuum oven at a constant temperature of 60 ° C to dry to obtain CFs-COOH;
[0069] In the third step, (1.8-2.5) mass fraction of SiC-OH@Kh550 and (0.8-1.3) mass fraction of CFs-COOH were dissolved in distilled water and stirred at 85°C for 6 hours. After the reaction was completed, it was washed three times with ethanol and distilled water and dried in vacuum at 60°C to obtain a composite three-dimensional nanocomposite material.
[0070] By adding three-dimensional nanocomposites with appropriate proportions to the mortar, mechanical meshing can be formed with the aggregate, increasing the contact area and contact layer thickness of the aggregate and nanomaterials inside the sample, effectively improving the chemical bonding and non-chemical bonding between the fiber and the matrix material, thereby effectively transmitting stress when the sample is loaded, enhancing the interface performance between the substrate and the nano-doping, and improving the mechanical strength and rigidity of the repair mortar. And the reasonable addition amount of silicon carbide and carbon fiber is verified by comparative tests. The comparative test is as follows: Under the premise that the other components of this mortar are the same, a control group is set up without adding three-dimensional nanocomposites. The ratio of silicon carbide to carbon fiber in experimental group 1 is 25:8; the ratio of silicon carbide to carbon fiber in experimental group 2 is 5:2; the ratio of silicon carbide to carbon fiber in experimental group 3 is 2:1; the ratio of silicon carbide to carbon fiber in experimental group 4 is 18:13; the ratio of silicon carbide to carbon fiber in experimental group 5 is 18:8; the mortar sample is prepared by the process of this scheme, and the mortar is a cubic mortar block of 100mm*100mm*100mm. The experimental results are as follows:
[0071]
[0072] The above experimental results show that the addition of three-dimensional nano-composite materials improves the compressive strength and bonding strength compared to not adding three-dimensional nano-composite materials. It is further shown that when the mass ratio of silicon carbide: carbon fiber meets 2:1, the compressive and bonding properties of the mortar reach the optimal level, and when the mass ratio of silicon carbide: carbon fiber is greater than 2:1, the compressive and bonding properties both decrease. Therefore, when the mass ratio of silicon carbide: carbon fiber meets 2:1, it helps to improve the overall structural performance of the mortar, with high bonding strength and good bonding with the original pavement.
[0073] Example 8
[0074] Compared with Example 7, the active silicon micropowder is prepared from waste smoke, and the specific treatment process of the waste smoke is as follows: first, the flue gas generated by the electric furnace is separated from the dust with high specific gravity by a gravity cyclone dust collector; then the high-temperature flue gas is passed through a flue gas water cooling tower to reduce the temperature, and the dust is further separated. The temperature of the flue gas after passing through the flue gas circulating water cooling tower is 45°C to 245°C; then the flue gas is discharged into a pipeline into a flue gas purification chamber, and the dust in the flue gas is collected by a fluoromethoxy filter bag through a sub-bin purification chamber in the flue gas purification chamber, and finally processed by a vortex centrifuge to obtain gaseous active silicon dioxide micropowder; the gaseous active silicon dioxide micropowder is sent to a powder storage tank for storage, and is treated and recovered at a temperature exceeding 100°C to obtain active silicon dioxide micropowder; then the silicon dioxide micropowder is modified, and the specific process is as follows: 1. A tetrahydrofuran solution of polydimethylsiloxane is prepared, wherein the mass concentration of polydimethylsiloxane is 2-8wt%. 1. Disperse spherical silicon micropowder in the solution, and the dispersion ratio of spherical silicon micropowder in the solution is (1-4) g / 100 mL; 2. Filter out the silicon micropowder after stirring and mixing, and vacuum dry it; 3. Heat the dried silicon micropowder to 400-600°C and keep it warm for 0.5-1h, then cool it to obtain active silicon micropowder.
[0075] Since there are a large number of Ca(OH)2 and free Ca2+, Mg2+ alkaline substances in cement, and since they are soluble in water, too much of these substances may affect the performance of the mortar. Reducing their content through chemical reactions can not only improve the strength of the mortar, but also enhance the density of the mortar. The active ingredients of the added active silica powder react with Ca(OH)2 and free Ca2+, Mg2+ and other substances in the cement at a specific concentration and osmotic pressure. With the action of water, these complexes diffuse into the mortar, and when encountering cement particles and cement gel, the active ingredients are replaced by more stable silicate ions to form water-insoluble and more stable crystalline substances. Water-insoluble crystalline substances such as calcium silicate and magnesium silicate are produced to fill pores and cracks, thereby improving the density of concrete. In a dry state, this material is dormant, but when cracks occur in the repair mortar and water invades, the active ingredients will be activated, penetrate with water and react to form healing products, automatically repairing microcracks and pores
[0076] By adding active silicon micropowder of appropriate proportion components into the mortar, when the repair mortar cracks and is immersed in water, the active ingredients will be activated, penetrate with water and react to generate healing products, automatically repair microcracks and pores, and play an automatic repair role. The reasonable addition amount of the three-micro-nano composite material and active silicon micropowder is verified by comparative experiments. The comparative experiment is as follows: Under the premise that the other components of this mortar are the same, the control group is set without adding active silicon micropowder. The ratio of silicon carbide to carbon fiber in experimental group 1 is 3:1; the ratio of silicon carbide to carbon fiber in experimental group 2 is 17:6; the ratio of silicon carbide to carbon fiber in experimental group 3 is 2:1; the ratio of silicon carbide to carbon fiber in experimental group 4 is 19:11; the ratio of silicon carbide to carbon fiber in experimental group 5 is 7:5. The mortar sample is prepared by the process of this scheme and dried. The mortar is a cubic mortar block of 100mm*100mm*100mm. The experimental results are as follows:
[0077]
[0078] The above experimental results show that compared with the mortar without active silicon powder, the mortar made by adding active silicon powder has obvious self-repairing ability, and the splitting tensile strength and carbonation resistance are improved. The addition of active silicon powder makes the internal structure of the mortar more compact and fills the pores, thereby reducing the entry of carbon dioxide into the mortar layer, improving the carbonation resistance, and increasing the durability of mortar repair. It is further shown that when the mass ratio of three-micro nano-composite materials: active silicon powder meets 5:2, the splitting tensile performance is the strongest, and when the mass ratio of three-micro nano-composite materials: active silicon powder meets 2:1, the carbonation resistance and repair ability are the strongest. Therefore, the comprehensive selection of the mass ratio of three-micro nano-composite materials: active silicon powder is 2:1, which is helpful to improve the overall structural performance of the mortar, the best crack resistance, the best durability, and the best self-repairing ability.
[0079] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. High-strength pavement repair mortar, characterized in that: It includes component A and component B; Component A is the main agent, and component B is the auxiliary agent; Component A includes the following components by mass: 350-550 parts of cement, 400-500 parts of aggregate, 0.5-2.0 parts of water reducer, 2-5 parts of dispersible latex powder, 0.1-0.5 parts of cellulose, 0.5-2.0 parts of defoamer, 0.5-1.0 parts of tartaric acid, and 200 parts of water. The cement is composed of sulphoaluminate cement and silicate cement in the ratio of (4-6): (3-5). Component B includes the following components by mass: 3.5-5.5 parts of waste smoke.
2. The high-strength pavement repair mortar according to claim 1, characterized in that: Component B also includes: 2.5-5.5 parts of three-dimensional nanocomposite material, and the mass ratio of silicon carbide to carbon fiber in the three-dimensional nanocomposite material satisfies (1.8-2.5): (0.8-1.3).
3. The high-strength pavement repair mortar according to claim 2, characterized in that: The preparation method of the three-dimensional nanocomposite material includes: the first step, silicon carbide powder modification, adding nano-scale silicon carbide powder to 0.2g / mL NaOH solution, stirring at a constant temperature of 85°C for 6h, washing with ethanol and deionized water until neutral, placing the cleaned nano-silicon carbide powder in a vacuum oven at a constant temperature of 85°C, and drying to obtain SiC-OH; taking the above-prepared SiC-0H and adding it to a mixture of anhydrous ethanol and distilled water, and ultrasonically dispersing it for 1h; adjusting the pH of the solution to 4-5 with formic acid, and then adding an appropriate amount of 3-aminopropyltriethoxysilane dropwise; stirring at 85°C for 24h to complete the reaction; washing with ethanol and distilled water three times, and then vacuum drying at 60°C to obtain SiC-OH@Kh550; The second step is carbon fiber modification. An appropriate amount of carbon fiber is added to an appropriate amount of hydrogen peroxide solution with a mass fraction of 30 wt%, stirred at a constant temperature of 50 ° C for 6 hours, washed three times with ethanol and deionized water, and the cleaned carbon fiber is placed in a vacuum oven at a constant temperature of 60 ° C to dry to obtain CFs-COOH; In the third step, (1.8-2.5) mass fraction of SiC-OH@Kh550 and (0.8-1.3) mass fraction of CFs-COOH were dissolved in distilled water and stirred at 85°C for 6 hours. After the reaction was completed, it was washed three times with ethanol and distilled water and dried in vacuum at 60°C to obtain a composite three-dimensional nanocomposite material.
4. The high-strength pavement repair mortar according to claim 1, characterized in that: The dispersible latex powder is a copolymer of vinyl acetate.
5. The high-strength pavement repair mortar according to claim 1, characterized in that: The aggregate comprises two kinds of river sands with different particle sizes, the particle sizes of the two kinds of river sands are 1-2 mm and 5-6 mm respectively, and the ratio thereof satisfies (1.5-2.5):(0.8-1.2).
6. The high-strength pavement repair mortar according to claim 1, characterized in that: The fibers consist of steel fibers and flax fibers in a ratio of 2:
4.
7. The high-strength pavement repair mortar according to claim 1, characterized in that: The defoamer is polyether silicone oil.